(untitled) (Research, Society and Development, 2023)
Rheumatoid Arthritis (RA) is an inflammatory and chronic autoimmune disease, which may be associated with other endocrine diseases that worsen the condition or make it difficult to manage this rheumatopathy. The objective of this research is to verify which are the most prevalent endocrinopathies in patients with RA, through a retrospective observational, analytical study, based on the analysis of medical records collected in the Specialty Center of the West region of Paraná in patients with association of these diseases. Among the main associated endocrine diseases, we found diabetes mellitus, dyslipidemia, osteoporosis and thyroid disease, with diabetes mellitus being the most prevalent, present in 21.42% of the analyzed cases, and osteoporosis the least prevalent, appearing in 7% of the medical records. It was concluded that the presence of endocrine diseases in patients with RA may be associated with the medications used in the management of RA, thus requiring stricter control over the use of medications such as methotrexate, glucocorticoids, leflunomide and hydroxychloroquine.